Association of dietary quality and dietary inflammatory potential with inflammatory markers: evidence from the national health and nutrition examination survey 2009-2018 - Sida Wang; Yujin Bao; Linning Wang; Xiaoxi Xie; Yun Lu (Frontiers in Immunology)
ObjectivesThis study aimed to investigate the independent and joint association of dietary quality and dietary inflammatory potential with four inflammatory markers among U.S. adults and to analyze the moderating role of age.MethodsThis study included 19,110 participants from the National Health and Nutrition Examination Survey (NHANES, 2009–2018). Dietary quality and dietary inflammatory potential were assessed using the Healthy Eating Index-2015 (HEI-2015) and the Dietary Inflammatory Index (DII), respectively, and thus classified into four dietary patterns. Inflammatory markers included white blood cell (WBC), neutrophil (Neu), neutrophil-to-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII). Weighted multiple linear regression and weighted quantile sum (WQS) regression were employed to analyze the relationships between HEI-2015/DII and inflammatory markers. Joint effect and interaction analyses were conducted to explore the impacts of different dietary patterns and age.ResultsHEI-2015 showed significant inverse associations with WBC, Neu, NLR, and SII, whereas DII exhibited significant positive associations with these markers. WQS analysis revealed that adequacy components in HEI-2015 such as seafood and plant proteins, and whole grains contributed most to reduced inflammation. In contrast, fiber, alcohol, and energy intake were the primary contributors to inflammatory markers in DII. Joint effect analysis demonstrated that compared to pattern 1, pattern 4 significantly reduced WBC, Neu, NLR, and SII levels. However, no significant reduction was observed in pattern 3. Additionally, age significantly strengthened the inverse associations between HEI-2015 and WBC/Neu, while weakening the positive associations between DII and SII.ConclusionImproving dietary quality and reducing dietary inflammatory potential may help lower inflammatory biomarker levels, with age playing a critical moderating role. High-quality diets can counteract the adverse effects of pro-inflammatory diets, whereas solely anti-inflammatory diets cannot compensate for the detrimental effects of low-quality diets. The combined effect of both approaches may further enhance anti-inflammatory outcomes.